Saint-Petersburg Experience of the First Russian Pediatric Hospice Organization - A. E. Tkachenko; S. A. Safonova; Yu. A. Punanov; S. I. Pridvizhkin; P. E. Ovsyanniova; L. A. Vorobyova; V. G. Tovpyga; O. A. Shargorodskaya (Медицинский вестник Юга России, 2010)
The authors of the article note the high rate of pediatric disabilities in Russia and describe the experience of Russia’s first organization actively acting in the field of pediatric social care and palliation under the auspices of the Russian Orthodox Church since 2003, “Pediatric hospice”. The article describe in detail the goals and functions of the pediatric hospice, its structure, actual experience of its different branches and departments. Coordinated work of inpatient department and home care teams allows increasing the quality of life of children with disabilities.